2019
DOI: 10.1007/s11030-019-09919-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure-aided drug development of potential neuraminidase inhibitors against pandemic H1N1 exploring alternate binding mechanism

Abstract: The rate of mutability of pathogenic H1N1 influenza virus is a threat. The emergence of drug resistance to the current competitive inhibitors of neuraminidase, such as oseltamivir and zanamivir, attributes to a need for an alternative approach. The design and synthesis of new analogues with alternate approach are particularly important to identify the potential neuraminidase inhibitors which may not only have better anti-influenza activity but also can withstand challenge of resistance. Five series of scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Inspecting the final docked poses helped identify typical noncovalent interaction patterns such as hydrogen bonds, ionic or saline bridges, van der Waals or hydrophobic interactions, all of which are commonly seen in reversible drug-receptor complexes. Not all observed drug-interacting residues at the active site were also reported in the literature [ 25 , 26 , 27 , 28 , 29 ]. This finding constitutes a key argument in favor of the five scaffolds in view of drug resistance by mutated residues.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Inspecting the final docked poses helped identify typical noncovalent interaction patterns such as hydrogen bonds, ionic or saline bridges, van der Waals or hydrophobic interactions, all of which are commonly seen in reversible drug-receptor complexes. Not all observed drug-interacting residues at the active site were also reported in the literature [ 25 , 26 , 27 , 28 , 29 ]. This finding constitutes a key argument in favor of the five scaffolds in view of drug resistance by mutated residues.…”
Section: Resultsmentioning
confidence: 91%
“…Finally, the 3D target models were inspected for completeness and the monomeric target structures were used for blind docking of all five SOMs. Sialic acid and zanamivir were included as references for re-docking studies and to compare the docked poses and computed data with their crystallographically known binding modes and measured activities [ 25 ]. Docking was performed in a grid box of 70 Å × 60 Å × 60 Å dimensions, i.e., a space which completely covers the active site of the NA.…”
Section: Methodsmentioning
confidence: 99%
“…The designing of novel neuraminidase inhibitors is very essential, which may withstand the challenges of resistance. Malbari and co-workers 86 have designed ( Fig. 13 ) five series of scaffolds (aurones, chalcones, cinnamic acid analogues, pyrimidine analogues and cinnamic acid linkages) based on virtual screening against H1N1 virus.…”
Section: Neuraminidase Inhibitors (Nais)mentioning
confidence: 99%
“…Many aurones have also been evaluated for their inhibitory activity against the glycoprotein neuraminidase, which is involved in the infection processes of the most common influenza viruses. In this case, the analysis of the structure–activity relationship showed that the key structural elements of the natural compounds, represented by a hydroxyl group in position 4 or 6 of the nucleus and a double bond in position 2, are essential for the activity [ 28 ].…”
Section: Aurones As Functional Agentsmentioning
confidence: 99%